ELECTRONIC ARBITRATION IN LEBANON – OVERVIEW AND TRENDS - Mira Fayad; Habib Kazzi (European Scientific Journal, ESJ, 2015)
Electronic arbitration (E-arbitration) is usually defined as a method to settle disputes through online platforms providing arbitration services. It constitutes a recent process dispute resolution mechanism between economic agents through the use of information and communication technology. Earbitration is inseparable from the growth of e-commerce and cross-border trade transactions. Contracting parties in such transactions expect a swift, cost-effective and efficient dispute resolution mechanism. It is no coincidence therefore that an increasing number of domestic legislations and international regulations adhere to the rules governing E-arbitration. The fact remains that, surprisingly, the Lebanese regulatory framework puts several obstacles to the successful implementation of E-arbitration in Lebanon. In this respect, this contribution endeavors to identify the scope of such obstacles, and discusses the solutions adopted in other legal frameworks.